Silica Content and Structure from Corncob Ash with Various Acid Treatment (HCl, HBr, and Citric Acid) - Gladys Ayu Paramita Kusumah Wardhani; Nurlela Nurlela; Mia Azizah (Universitas Jenderal Soedirman, 2017)
In this study, a simple method to obtain silica from corncob ash has been investigated using a nonthermal and thermal method. The Nonthermal method was done by various acid treatment with HCl, HBr and citric acid at room temperature. Thermal method was performed for HCl-leached, HBr-leached, and citric acid-leached corncob in the furnace at 750 ºC for 5 hours. Corncob ash was characterized by Energy Dispersive X-ray fluorescence spectroscopy (EDXRF), Fourier transforms infrared spectroscopy (FTIR), X-Ray diffraction (XRD), and Scanning electron microscope-electron dispersive X-ray (SEM-EDX). In this study silica content increase after acid treatment (leaching) and combustion at high temperatures. The result established that silica is most obtained with HCl treatment that is equal to 79,95% with lower metallic oxide impurity content. The FTIR spectra with different intensity shows silanol group at 1636 – 1641 cm-1, whereas siloxane group at 1037 – 1106 cm-1, 616–797 cm-1, and 459–469 cm-1. X-Ray diffractogram shows silica transition pf amorphous (2θ = 21 - 25º) to quartz crystalline (2θ = 26.66º) phase. The surface morphology of silica that characterized with SEM-EDX shows amorphous and crystalline silica corresponds to XRD result. The high intensity spectra of Si and O in EDX shows the presence of silica in corncob ash.